Inflammation-related adverse reactions following vaccination potentially indicate a stronger immune response. Issue 1 (1st January 2021) - Zhuang, Chun-Lan; Lin, Zhi-Jie; Bi, Zhao-Feng; Qiu, Ling-Xian; Hu, Fang-Fang; Liu, Xiao-Hui; Lin, Bi-Zhen; Su, Ying-Ying; Pan, Hui-Rong; Zhang, Tian-Ying; Huang, Shou-Jie; Hu, Yue-Mei; et al.
ABSTRACT: Concerns about vaccine safety are an important reason for vaccine hesitancy, however, limited information is available on whether common adverse reactions following vaccination affect the immune response. Data from three clinical trials of recombinant vaccines were used in this post hoc analysis to assess the correlation between inflammation-related solicited adverse reactions (ISARs, including local pain, redness, swelling or induration and systematic fever) and immune responses after vaccination. In the phase III trial of the bivalent HPV-16/18 vaccine (Cecolin®), the geometric mean concentrations (GMCs) for IgG anti-HPV-16 and -18 ( P <0.001) were significantly higher in participants with any ISAR following vaccination than in those without an ISAR. Local pain, induration, swelling and systemic fever were significantly correlated with higher GMCs for IgG anti-HPV-16 and/or anti-HPV-18, respectively. Furthermore, the analyses of the immunogenicity bridging study of Cecolin® and the phase III trial of a hepatitis E vaccine yielded similar results. Based on these results, we built a scoring model to quantify the inflammation reactions and found that the high score of ISAR indicates the strong vaccine-induced antibody level. In conclusion, this study suggests inflammation-related adverse reactions following vaccination potentially indicate a stronger immune response.